Seismic Design of Hospital Buildings : A Comparative Study of Base Isolated Systems Using IS 1893 (2016) and ASCE-7 (2022) - Satapathy, Prabina Kumar; Parhi, P. K. (AMC Indian Journal of Civil Engineering, 2024)
The present study focuses on the seismic design and performance evaluation of base-isolated hospital buildings in India, with a particular focus on the actual application of Indian standards IS 1893 (Part 1) and IS 1893 (Part 6). The analysis includes a thorough review of the study areas of the seismic activity and the resilience of the existing hospital facilities. The study performs advanced nonlinear time-history analysis to evaluate the seismic responses of base-isolated structures. The data suggest that base-isolated buildings have significantly lower accelerations and inter-story drifts, resulting in less structural and non-structural damages during seismic events. The data demonstrate that base isolation improves earthquake protection and operational continuity in hospital facilities. The report also identifies critical design features of the Indian standards. The study also identifies the critical design elements of the Indian standards, highlighting the significance of specialized seismic mitigation systems over fixed base buildings.